2019
DOI: 10.1093/ibd/izz009
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Epithelial Surfactant Protein D Expression Correlates with Inflammation in Clinical Colonic Inflammatory Bowel Disease

Abstract: BackgroundInflammatory bowel diseases (IBD) are chronic disorders of the gastrointestinal tract. Surfactant protein D (SP-D) is expressed in the intestinal epithelium and is essential for innate host defense and regulation of inflammatory responses. Genetic variations of SP-D are associated with IBD, but the effects of SP-D in clinical disease development have not been clarified. We hypothesized that colonic epithelial SP-D expression is increased in parallel with intestinal inflammation with the capacity to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In a recent study by Sarashina-Kida et al (108), it was shown that SP-D could also originate from the gallbladder, where it had an anti-inflammatory role in a dextran sulfate sodium (DSS)-induced murine colitis. However, Nexoe et al (109) performed a similar study and could not replicate the anti-inflammatory role of SP-D in the DSS-model. Regardless, the conclusion is that SP-D not only originates from the lung but can be secreted by various sources, such as the arteries and gallbladder.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study by Sarashina-Kida et al (108), it was shown that SP-D could also originate from the gallbladder, where it had an anti-inflammatory role in a dextran sulfate sodium (DSS)-induced murine colitis. However, Nexoe et al (109) performed a similar study and could not replicate the anti-inflammatory role of SP-D in the DSS-model. Regardless, the conclusion is that SP-D not only originates from the lung but can be secreted by various sources, such as the arteries and gallbladder.…”
Section: Discussionmentioning
confidence: 95%
“…Some potential evidence has carried out the link between SFTPD and phylum Proteobacteria . Nexoe et al, found a strong positive correlation between inflammatory activity and expression of SFTPD in the intestinal epithelium from Inflammatory Bowel Disease (IBD) patients [ 44 ], while the increase of Proteobacteria is one of the most consistent observations in IBD individuals [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stainings were performed in parallel with validation controls using CHO cells expressing recombinant full-length FIBCD1 ( 13 ) and representative non-cancerous human colon specimens using an optimized protocol described previously ( 12 ). The semiquantitative immune score for FIBCD1 expression was performed on specimens obtained from 35 patients clinically diagnosed with CRC stage I (n=8), II (n=19), and III (n=8) using a scoring system consisting of a distribution score and an intensity score, as described previously ( 21 ). The FIBCD1 positive epithelial cell distribution was scored from 0 to 4 as follows: 0, less than 10% of the epithelial cells were positive for FIBCD1; 1, 10%–30% of the epithelial cells were positive for FIBCD1; 2, 31%–60%, 3, 61-90%, and 4, >90% of the epithelial cells were positive for FIBCD1.…”
Section: Methodsmentioning
confidence: 99%